Cognitive neuroscience : the biology of the mind. - Gazzaniga, Michael S., 1939-; Ivry, Richard B., ....-; Mangun, George R., ....-; Steven, Megan S., ....- (New York : Norton, 2009)
Three leading figures in the field of cognitive neuroscience provide an engaging, narrative driven overview of this path-breaking field. Taking a highly interdisciplinary approach, the authors balance cognitive theory, with neuroscientific and neuropsychological evidence to reveal what we currently know about how the human mind works and to encourage students to think like cognitive neuroscientists. The text has been reorganized to move more seamlessly from micro to macro level topics, and its underlying pedagogy strengthened in order to make it an even more effective teaching tool. Maintaining its commitment to highlight the most cutting-edge trends in the field, the third edition includes the first ever standalone chapter of its kind on social neuroscience.
Inhoudsopgave : Part 1: Background and Methods Chapter 1 - A Brief History of Cognitive Neuroscience Chapter 2 - The Cellular and Molecular Basis of Cognition Chapter 3 - Neuroanatomy and Development Chapter 4 - The Methods of Cognitive Neuroscience Part 2: Core Processes Chapter 5 - Sensation and Perception Chapter 6 - Object Recognition Chapter 7 - Action Chapter 8 - Learning and Memory Chapter 9 - Emotion Chapter 10 - Language Chapter 11 - Hemispheric Specialization Part 3: Control Processes Chapter 12 - Attention and Consciousness Chapter 13 - Executive Function Chapter 14 - The Social Brain Chapter 15 - Evolutionary Perspectives
Vakgroep Experimentele Psychologie (PP02)
Keywords: Neurologie